Superparamagnetic iron oxides and low molecular weight gadolinium chelates are synergistic for direct visualization of advanced liver fibrosis - Hughes-Cassidy, Fiona; Chavez, Alyssa D.; Schlang, Adrienne; Hassanein, Tarek; Gamst, Anthony; Wolfson, Tanya; Sirlin, Claude (Journal of magnetic resonance imaging, 2007)
Purpose To compare the contrast‐to‐noise ratio (CNR) of advanced liver fibrosis on nonenhanced (NE), gadolinium enhanced (Gd), superparamagnetic iron oxides enhanced (SPIO), and combined contrast‐enhanced (CCE) spoiled gradient echoes (SGEs). Materials and Methods This retrospective study assessed 83 consecutive patients with cirrhosis and 10 consecutive patients without fibrosis. All patients had NE, Gd, SPIO, and CCE images at 1.5T. A total of six breathhold SGE sequences with varying imaging parameters were assessed. MR images were evaluated qualitatively and, in 15 cirrhotics who underwent liver transplantation, compared to gross pathology. CNR of fibrosis to background liver was compared across sequences and contrast enhancement types. Results In cirrhotic patients, CCE images on all sequences showed fibrosis as a meshwork of high‐signal 1‐mm to 3‐mm thick reticulations surrounding 2‐mm to 5‐mm low‐signal regenerative nodules. Fibrosis was less visible on Gd and SPIO images and was barely visible on NE images. CNR was significantly higher for CCE than for NE, Gd, or SPIO images in eight of nine comparisons (P < 0.0001–0.05). The liver had a homogeneous appearance in subjects without fibrosis. Conclusion CCE imaging depicts advanced liver fibrosis with higher CNR than NE, Gd, or SPIO SGEs. J. Magn. Reson. Imaging 2007. © 2007 Wiley‐Liss, Inc.